Pacific women's netball participation in Aotearoa/New Zealand : factors influencing participation : a thesis presented in partial fulfilment of the requirements for the degree of Masters in Business Studies in Sports Management at Massey University - Teevale, Tasileta (Massey University, 2001)
The purpose of this study was to explore the netball experiences of Pacific women in Aotearoa/New Zealand. Specific objectives were to identify reasons for participation, socialisation agents and the link between ethnicity and sport. A mixed-method approach was utilised to gather data. 157 netballers (age range 17-56+) completed a modified version of the Participation Motivation Questionnaire (Gill, Gross & Huddleston, 1983). Treatment of the scores by principal components analysis yielded seven factors: Aspects of Netball/Health & Fitness, Challenge, Social Status, Affiliation, Energy Release, Skills Development, and Family Affiliation. Focus group data (3 groups) confirmed the family as the most significant socialisation agent during initial involvement, and the salience of self-motivation for current participation. In addition, netballers articulated the existence of a "Pacific" style of play, which the author hypothesised, reflects the affects of a unique cultural background and sporting environment. The key implication of this research is the need for sport managers to deliver sport opportunities that meet the diverse needs of its multi-ethnic and multi-cultural participants in order to ensure continued participation. Areas for future research are identified.
Keywords: Netball; Women netball players; Pacific Islanders; New Zealand